Will mark brainliest! Which of the following is the result of using the remainder theorem to fin F(-2) for the polynomial functi

Question

Will mark brainliest!

Which of the following is the result of using the remainder theorem to fin F(-2) for the polynomial function F(x)=-2x^3+x^2+4x-3?

A. -23
B. 9
C. -11
D. 3

in progress 0
Yến Oanh 6 months 2021-09-04T07:52:33+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-09-04T07:53:36+00:00

    Answer:

    B

    Step-by-step explanation:

    To find f(- 2) substitute x = – 2 into f(x)

    f(- 2) = – 2(- 2)³ + (- 2)² + 4(- 2) – 3

            = – 2(- 8) + 4 – 8 – 3

            = 16 + 4 – 8 – 3

            = 9 → B

  1. Answer:

    i think its 3

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )